Physical and Data-Link Security Techniques for Future Communication Systems - Baldi, Marco; Tomasin, Stefano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on techniques that can be applied at the physical and data-link layers of communication systems in order to secure transmissions against eavesdroppers. Topics ranging from information theory-based security to coding for security and cryptography are discussed, with presentation of cutting-edge research and innovative results from leading researchers. The characteristic feature of all the contributions is their relevance for practical embodiments: detailed consideration is given to applications of security principles to a variety of widely used communication techniques such as multiantenna systems, ultra-wide band communication systems, power line communications, and quantum key distribution techniques. A further distinctive aspect is the attention paid to both unconditional and computational security techniques, providing a bridge between two usually distinct worlds. The book comprises extended versions of contributions delivered at the Workshop on Communication Security, held in Ancona, Italy, in September 2014 within the framework of the research project "Enhancing Communication Security by Cross-layer Physical and Data-link Techniques", funded by the Italian Ministry of Education, Universities, and Research.
Physical Layer Security: a Paradigm Shift in Data Confidentiality -- Secure Communication in Wiretap Channels with Partial and Statistical CSI at the Transmitter -- MIMOME Gaussian Channels with GMM Signals in High-SNR Regime: Fundamental Limits and Tradeoffs -- Performance Analysis of Transmission Over AWGN Wiretap Channels With Practical Codes -- Broadcast Channels with Confidential Messages: Channel Uncertainty, Robustness, and Continuity -- End-to-End Key Establishment with Physical Layer Key Generation and Specific Attacker Models -- Experimental Results on Secret-Key Extraction from Unsynchronized UWB Channel Observations -- Physical Layer Security in Power Line Communication Networks -- Security Aspects of Compressed Sensing -- Subspace Fuzzy Vault -- An Information Rate Improvement For a Polynomial Variant of the Naccache-Stern Knapsack Cryptosystem -- Implementation and Improvement of the Partial Sum Attack on 6-round AES -- A Real Life Project in Cryptography: Assessment of RSA Keys -- Encoding in The DTMF Channel for Two-Channel Authentication.
Keywords: Telecommunication; Data protection; Signal processing; Communications Engineering, Networks; Data and Information Security; Signal, Speech and Image Processing